Организаційна форма інноваційного розвитку - Ковальов, Є. В. (НТУ "ХПІ", 2014)
Визначено, що для сучасного економічного становища України збереження переважно сировинного напрямку господарської діяльності має високий рівень економічної небезпеки. Доведено - перспективною організаційною формою підприємства, спроможного забезпечити інноваційний розвиток, конкурентоспроможність на світових ринках і зміцнення економічної безпеки України, є українська корпорація.

The study found that the raw direction of economic development, in which moves Ukraine, contrary to global trends, the country has a high level of economic risks and, of course, should be replaced by innovative direction. Experience shows - the best opportunities for innovation are large enterprises. Modern Ukraine’s position on the priority development of small and medium-sized enterprises is estimated to be in error. It is advisable to optimal ratio and competitive coexistence of large, medium and small businesses. To ensure the innovative development is proposed wider use of economic activity organizational form of the corporation.
Organizational form of innovative development
Keywords: підприємство; економічна безпека держави; "сировинна" економіка; корпорація; enterprise; economic security of the state; "raw" economy; innovation development; corporation